Grounding Adult Education Research in Rural Areas: Reflections on the Development of a Research Program at the University of Limpopo in South Africa. (February 2014) - Zeelen, Jacques; Rampedi, Makgwana; van der Linden, Josje
Mission statements of universities in developing countries usually include serving the surrounding communities. Often this service does not reach beyond lip service. This article puts into context the experience of developing an adult education research program responding to the needs of the surrounding community in a historically disadvantaged rural area. The areas of research were adult education needs assessment and community development, young adults at risk, adult health education, and policy and implementation issues. Globalization, social exclusion, and lifelong learning were key concepts tailored to the specific context of the rural areas in South Africa. The first two authors of the article were personally involved in the program, as a visiting professor from the Netherlands and his South African successor, respectively. The third author worked in a similar program at the Eduardo Mondlane University in Maputo, Mozambique.